WADY WRODZONEEffects of delayed sternal closure for the post-operative period in children with hypoplastic left heart syndrome after a modified Norwood operation - Składzień, Tomasz; Kołcz, Jacek; Wójcik, Elżbieta; Skalski, Janusz H. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Delayed sternal closure is a procedure used following pediatric cardiopulmonary bypass surgery for many reasons. There is a debate whether primary or delayed sternal closure is the best strategy following the Norwood procedure for hypoplastic left heart syndrome. We reviewed 88 patients with hypoplastic left heart syndrome after stage 1 Norwood procedure at the Department of Pediatric Cardiac Surgery, Polish-American Institute of Pediatrics, Jagiellonian University in Cracow. Delayed sternal closure was employed in 36 of 88 patients (40.9%). Children with delayed sternal closure showed a longer average duration of stay in the ICU (36.58 ±34.8 days) and total hospitalization (63.58 ±47.9 days) as compared to children with primary sternal closure (22.83 and 49.13 ±49.7 ±60.8 days, respectively). We also observed a significantly longer mean time of mechanical ventilation in the postoperative period (453.85 ± 72 hours) in patients in whom delayed sternal closure was used as opposed to the second group (142.14 ±109.5 hours). There was noted a statistically significant relationship between the length of time of cardiopulmonary bypass (the average in the group with delayed sternal closure was 06.92 ±43 min, and in the group with primary sternal closure 76.73 ±18.2 min). Delayed sternal closure should not be used as a routine postoperative procedure because it is associated with medical complications, such as wound infections, as well as increased costs of treatment.